STRATEGIES OF IMPLEMENTATION OF THE CAPACITIES OF THE GOVERNMENTAL APPLICATIONS IN PROVIDING QUALITY OF PUBLIC SERVICES - Ade Risna Sari (Adisam Publisher, 2024)
In an era of globalization and rapid information technology development, the demand for quality public services is increasing. As a major public service provider, governments are faced with the challenge of increasing the capacity of equipment to deliver responsive, efficient, and community-sensitive services. The study aims to examine strategies for the development of the capacity of government apparatus in the realization of quality public services. This investigation uses the study of literature by searching for references that fit the context of the research. The results show that the development of capacity of government apparatus requires a comprehensive approach involving a wide range of stakeholders, as well as policies that support adaptation to change and accommodate the needs of the public. The study provides recommendations to policy makers to strengthen capacity development initiatives with the aim of achieving quality public services and building public confidence in the government.